STUDI KASUS : PENANGANAN SCHOOL-REFUSAL PADA SISWA SEKOLAH DASAR (SD) BERBASIS KELUARGA - Titisa Balerina (LP2M Universitas Sarjanawiyata Tamansiswa, 2018)
School-refusal behavior is defined as absenteeism in schools, there are barriers to leaving for school or barriers to being in school. Interventions to deal with school-refusal behavior can be done in school settings, families and on children directly. This case study aims to implement family-based school-refusal interventions. The main question in this study is how to improve the presence of children who experience school-refusal? The process has been done are: (1) assess the subject; (2) analyze the problem; (3) arrange interventions for the subject; (4) implementing interventions; (5) evaluating the effect of intervention. The conclusion of this study is that there is an increase in school attendance after family-based interventions. The conclusion of this study is that school-refusal intervention in elementary school children requires cooperation between family and school.